Lactic Acid Bacteria Biota and Aroma Profile of Italian Traditional Sourdoughs From the Irpinian Area in Italy - Reale, Anna; Di Renzo, Tiziana; Boscaino, Floriana; Nazzaro, Filomena; Fratianni, Florinda; Aponte, Maria (Frontiers in Microbiology, 2019)
This study identified the lactic acid bacteria (LAB) biota and the volatilome profile of 28 typical sourdoughs of Irpinia—a large area of the Campania region of Southern Italy where numerous breads are produced, even today, following the ancient procedures of sourdough fermentation and for which information on the microbiological and sensory profile is lacking in literature. For this purpose, microbial quality, LAB biodiversity, chemical, and technological characteristics, as well as aroma profile by solid-phase microextraction technique (SPME)–gas chromatography/mass spectrometry (GC/MS) of Irpinian sourdoughs were investigated. The dominant LAB microbiota was examined by both culture-dependent and culture-independent methods Polymerase Chain Reaction/Denaturing Gradient Gel Electrophoresis (PCR-DGGE). Results showed a high biodiversity in LAB community whereas the most frequent lactobacilli species recognized were Lactobacillus plantarum (ca. 22% of total LAB isolates), Lactobacillus sanfranciscensis (11%), Lactobacillus paralimentarius (8%), and Lactobacillus rossiae (6.5%), whereas LAB cocci could be mainly referred to Pediococcus pentosaceus (9.5% of total LAB isolates), Leuconostoc spp. (7.8%), and Weissella cibaria (7.7%). Sourdoughs were characterized by the dominance of one or two LAB species, thus proving that the environment influences the selection and the establishment of few key LAB species and that no specific correlation can be traced between microbial composition and geographical origin of the samples. Furthermore, although sourdoughs were characterized by different qualitative and quantitative volatile organic compound (VOC) compositions, no noticeable correlation between volatilome profile and geographical origin was found. However, it emerged that for more isolated locations, it was possible to find the existence of microbial biotypes and sensory profiles with a strong identity, thus revealing the existence of highly traditional and evocative bread recipes in those geographical contexts.